Vibrio parahaemolyticus Strains of Pandemic Serotypes Identified from Clinical and Environmental Samples from Jiangsu, China - Li, Jingjiao; Xue, Feng; Yang, Zhenquan; Zhang, Xiaoping; Zeng, Dexin; Chao, Guoxiang; Jiang, Yuan; Li, Baoguang (Frontiers in Microbiology, 2016)
Vibrio parahaemolyticus has emerged as a major foodborne pathogen in China, Japan, Thailand and other Asian countries. In this study, 72 strains of V. parahaemolyticus were isolated from clinical and environmental samples between 2006 and 2014 in Jiangsu, China. The serotypes and six virulence genes including thermostable direct hemolysin (TDR) and TDR-related hemolysin (TRH) genes were assessed among the isolates. Twenty five serotypes were identified and O3:K6 was one of the dominant serotypes. The genetic diversity was assessed by multilocus sequence typing (MLST) analysis, and 48 sequence types (STs) were found, suggesting this V. parahaemolyticus group is widely dispersed and undergoing rapid evolution. A total of 25 strains of pandemic serotypes such as O3:K6, O5:K17 and O1:KUT were identified. It is worth noting that the pandemic serotypes were not exclusively identified from clinical samples, rather, nine strains were also isolated from environmental samples; and some of these strains harbored several virulence genes, which may render those strains pathogenicity potential. Therefore, the emergence of these “environmental” pandemic V. parahaemolyticus strains may poses a new threat to the public health in China. Furthermore, six novel serotypes and 34 novel STs were identified among the 72 isolates, indicating that V. parahaemolyticus were widely distributed and fast evolving in the environment in Jiangsu, China. The findings of this study provide new insight into the phylogenic relationship between V. parahaemolyticus strains of pandemic serotypes from clinical and environmental sources and enhance the MLST database; and our proposed possible O- and K- antigen evolving paths of V. parahaemolyticus may help understand how the serotypes of this dispersed bacterial population evolve.